Controversies and current practices in CNS relapse of diffuse large B-cell lymphoma (Canadian Hematology Today, 2022)
Central nervous system (CNS) relapse is an uncommon complication of diffuse large B-cell lymphoma (DLBCL), occurring in approximately 3–5% of patients and at a median timepoint of 6–9 months from diagnosis. Approximately half of these cases present as isolated CNS relapse caused by occult seeding of the CNS early in the disease course, while the remaining cases occur in the context of concurrent systemic relapse. The median survival after CNS relapse is only 4–6 months, highlighting the unmet need to identify effective prophylaxis and management strategies. This article provides an overview of current controversies and optimal strategies for prognosticating, preventing, and treating CNS relapse in patients with DLBCL.